Exploring Relational Professionalism in Schools - Frelin, Anneli; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2013)
How is it that some teachers have just (3z(Bgot it(3y(B? They walk into a room and the atmosphere changes. They get through to students in a way that no-one else can. The author has sought answers to this question by observing and interviewing teachers from preschool to upper secondary school levels. Having intensively studied the highly influential but underestimated relational dimension of teaching, her contention is that these teachers successfully use relational practices to build educational relationships with their students and educational communities among them. Moreover, she finds that what may come across as a teacher$1 (Bs personal traits is actually a sensible professional approach. These teachers haven$1 (Bt (3z(Bgot it(3y (B- they (3z(Bget it(3y(B. This book explains how teachers carry out their relational practices, and contains an abundance of everyday examples from all stages of education. The deep theoretical reasoning departs from these examples to create a compelling argument for a teacher$1 (Bs relational professionality that is possible to learn and teach. New relational perspectives and concepts are introduced for the purpose of facilitating professional conversations about the profound dimension of relationships in education.s
Keywords: Education; Education; Education (general).